DESAIN PENGEMBANGAN UNIT PENGOLAHAN LIMBAH PLASTIK PADA KELOMPOK PEMULUNG DI KOTA MALANG - Widjanarko Widjanarko; Nilawati Fiernaningsih; Pudji Herijanto (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Types of waste issued by industries and communities are organic and non-organic. Non-organic waste can not decompose naturally but it needs human effort to process it by recycling, one of which is plastic waste. The method is the identification and formulation of problems in landfills / TPS and scavengers, then determined the purpose of the study. By literature study and field study can be concluded that the concept of a suitable problem solving is the method of Quality Function Deployment (QFD). Implementation of QFD in this study to determine the scavengers desire in improving the economic level, by distributing questionnaires to scavengers in Malang. The conclusion of this research is that scavengers want to increase their economic level by adding value to plastic waste. The value added criterion in this research is the increase of plastic waste price from ± Rp 6.000,00 / kg to ± Rp 12.000,00 / kg in the form of chopped. Design of product development of plastic waste cutter machine desired by the user / scavengers at an affordable price of 84.33% and in terms of capacity 72.33%, is a machine with a price of Rp 5,500,000.00 and a capacity of 10 kg / hour. Keywords: Plastic Waste, Scavengers, Economic Level, Affordable price, Capacity